Valoración de las acciones en el área de Evaluación de los Aprendizajes, Escuela de Ciencias Exactas y Naturales, periodo 2020-2022 (Repertorio Científico, 2024)
: This paper assesses the actions carried out in the Learning Evaluation Project of the ECEN Strategic Plan 2020-2024, which is oriented towards the continuous improvement of the evaluation processes in all subjects offered at the School of Exact and Natural Science (ECEN). The self-assessment is carried out by a committee in charge of developing and monitoring it during the period of 2020-2022. The materials and methods focus on the application of diagnosing training needs, the planning and development of activities to cover these shortcomings and the assessment carried out by the school’s academic staff of Exact and Natural Science. As a main conclusion, the strengthening of the evaluation of learning among academics is a continuous process and should be part of the strategic plan of each academic institution